Runoff estimation of Banaras Hindu University South Campus using ArcGIS and HecGeo-HMS - Shivhare N.; Omar P.J.; Gupta N.; Dikshit P.K.S. (My University, 2025)
Water is one of the most incredible natural resource which is vitally important for entire species of living beings present on the planet Earth. Therefore managing water resource is very necessary. Watershed modelling is to organize the watershed such that all the water related problems like water scarcity and flooding can be eliminated. Runoff is the most primary feature that is needed when planning water control strategies like water conservation structures, waterways and erosion control structures etc. Runoff estimation is essential for completing and executing plans, programs and tasks to support and expand watershed utilities. The most accepted technique to measure runoff or water discharge is Soil Conservation Service-Curve Number (SCS-CN) method. This project is dominant because here curve number is calculated on the basis of the properties of Land Use/ Land cover and soil type of the study area. Here Banaras Hindu University's (BHU) South Campus is taken as study area and curve numbers was calculated using HecGeo-HMS tool and by the help of softwares like ArcGIS and Erdas imagine runoff estimation and watershed modelling are done. This project highlights the role of Geographical Information System (GIS) and Remote Sensing (RS) on calculating Runoff using overlay techniques. Daily rainfall for ten years and LISS-IV satellite image is the data used in this project. And then the calculated Curve number can be used for runoff estimation and watershed modelling. © 2016 IEEE.